Production of melamine using the electrolysis method - Muminov, B.S.; Karimov, M.U. Karimov; Djalilov, A.T.; Khaitov, B.T. (Recent Contributions to Physics, 2024)
Melamine is the most important raw material in the paint industry and in the production of plastics. Melamine is also widely used in electrical engineering and textiles. Such widespread use has led to rapid growth in melamine production worldwide. The products of the organic synthesis industry are used in many fields and differ from other industrial products due to their different structure. Currently, the synthesis of melamine is carried out at high pressures and high temperatures or in the presence of catalysts, which complicates the technology. In this article, the technology of obtaining melamine using the electrolysis method is studied. The characteristics and schematic structure of the experimental device are presented. The synthesized melamine was analyzed using IR spectroscopy and NMR spectroscopy to confirm its chemical composition and structural properties. The IR spectra revealed characteristic peaks corresponding to primary amine groups and the triazine ring, confirming successful melamine synthesis. The study demonstrates the feasibility and advantages of using electrolysis for melamine synthesis, including reduced environmental impact and simplified technological processes. This innovative method holds significant potential for industrial application, offering a more economical and eco-friendly solution for the production of melamine and other organic compounds.